Odpowiedź :
a)
[tex](x+3)(x+5)=-4(x^2+2)+5x^2\\\\x^2+5x+3x+15=-4x^2-8+5x^2\\\\x^2+8x+15=x^2-8\\\\x^2+8x-x^2=-8-15\\\\8x=-23 \ \ /:8\\\\\huge\boxed{x=-2\frac{7}{8}}[/tex]
b)
[tex](x-2)(4+x)=x(x-5)\\\\4x+x^2-8-2x=x^2-5x\\\\x^2+2x-8=x^2-5x\\\\x^2+2x-x^2+5x=8\\\\7x=8 \ \ /:7\\\\\huge\boxed{x=1\frac{1}{7}}[/tex]
c)
[tex]-2x(x+1)=(3-2x)(x+2)\\\\-2x^2-2x=3x+6-2x^2-4x\\\\-2x^2-2x=-2x^2-x+6\\\\-2x^2-2x+2x^2+x=6\\\\-x=6 \ \ /:(-1)\\\\\huge\boxed{x=-6}[/tex]
d)
[tex](x-3)(x+3)=(x-2)^2\\\\x^2+3x-3x-9=(x-2)(x-2)\\\\x^2-9=x^2-2x-2x+4\\\\x^2-9=x^2-4x+4\\\\x^2-x^2+4x=4+9\\\\4x=13 \ \ /:4\\\\\huge\boxed{x=3,25}[/tex]